Load‐modulation technique without using quarter‐wavelength transmission line. Issue 11 (12th June 2020) - Abdulkhaleq, Ahmed M.; Yahya, Maan A.; Parchin, Naser O.; Al‐Yasir, Yasir; Sajedin, Maryam; Elfergani, Issa; McEwan, Neil J.; Abd‐Alhameed, Raed A.; Rayit, Ashwain; Rodriguez, Jonathan
Abstract : A proposed method for achieving active load‐modulation technique without using a quarter‐wavelength transmission line is discussed and evaluated. The theoretical analysis shows that the active load‐modulation can be achieved without using a quarter‐wavelength line, where the main amplifier sees a low impedance when the input signal level is low, and this impedance increases in proportion to the amount of current contributed from the peaking amplifier. The peaking amplifier sees an impedance decreasing from infinity to the normalized impedance. To validate the method, a circuit was designed, simulated and fabricated using two symmetrical gallium nitride (GaN) transistors (6 W) to achieve a peak power of 12 W and 6 dB output back‐off efficiency. The design operates with 400 MHz bandwidth at 3.6 GHz and showed an average efficiency of 50% at 6 dB back‐off and an efficiency of 75% at peak power. The designed circuit was tested with CW and modulated signals, the amplifier showed an Adjacent Channel Power Ratio (ACPR) of 31–35.5 dB when tested with a wideband code division multiple access signal of 6 dB peak‐average‐power ratio (PAPR) at 35.5 dBm average power. Additional 20 dB of linearity improvement was achieved after adding a lineariser.